Pesan dakwah di Akun TikTok Aab Elkarimi: Analisis Semiotika Charles Sanders Peirce - Muhammad Aulia Firman; Chairiawaty; Parihat Kamil (UNISBA Press, 2023)
Abstract. This research is motivated by the development of social media as a means of preaching and to understand what da'wah messages are contained in the Tiktok video